1995
DOI: 10.1007/bf02908845
|View full text |Cite
|
Sign up to set email alerts
|

Hormones-induced modifications in the response of wheat flag leaf to NaCl

Abstract: A field experiment was carried out to investigate the effects of presoaking the wheat grains (Triticum aestivum L.) in 33 or 66 mM NaC1 and indolyl-3-acetic acid (IAA at 50 g m-3), gibberellic acid (GA 3 at 100 g m -3) or kinetin (100 g m -3) on some tolerance criteria in wheat flag leaf at different stages of development. At various stages of flag leaf development pretreatment with 33 or 66 mM NaCI decreased degree of succulence (particularly 66 mM), relative growth rate, net assimilation rate, relative water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…concentration as compared to salinized plants. These results agree with Aldesuquy (1995) who reported that GA 3 reduced the accumulation of toxic ions in plant tissues under saline conditions; and Athar et al (2008) who suggested that the protection of wheat plants against salt stress by an exogenous supply of AsA is caused indirectly as a result of its effect on K ? uptake, which plays an essential role in many metabolic processes.…”
Section: Discussionsupporting
confidence: 93%
“…concentration as compared to salinized plants. These results agree with Aldesuquy (1995) who reported that GA 3 reduced the accumulation of toxic ions in plant tissues under saline conditions; and Athar et al (2008) who suggested that the protection of wheat plants against salt stress by an exogenous supply of AsA is caused indirectly as a result of its effect on K ? uptake, which plays an essential role in many metabolic processes.…”
Section: Discussionsupporting
confidence: 93%
“…Results from this study showed that with an increase in salt concentration, Na + was increased, while K + and Ca 2+ ions were decreased. GA priming reduced the concentration of toxic ions like Na + in some treatments and also increased K + but the increase was not significant; the results correlate with Aldesuquy (1995) who described that priming with GA3 reduced the accumulation of Na + and increased K + /Na + ratio in flag leaves of wheat under salt treatments. Possibly it is due to antagonistic effect of ionic pumps located at membranes that allows certain level of a particular ion to enter; hence the Na + being cation will definitely remove some K + to compensate itself in the cell.…”
Section: Discussionsupporting
confidence: 78%